Super potato design : the complete works of Takashi Sugimoto Japans leading interior designer / By Mira Locher foreward by Tadao Anda - LOCHER, Mira; Anda, Tadao (Tuttle Publishing, 2008)
240 hlm. : ilus. ; 26 cm. [2 eks.]